Qur’anic argumentation on the topic of the Hereafter between rational logic, value-based inference, and emotional impact - soltani, Muhammad (El Omda in Linguistics and Discourse Analysis, 2025)
This research approaches some of the persuasive argumentative dimensions in one of the most important topics revolving in the nobe Qur’an, which is the discourse of the afterlife; That discourse, which is a unique model of the miraculous Qur’anic rhetoric, with its conclusive demonstrative evidence, wonderful dialogue scenes, and a captivating pictorial narration.It is a research in which we show one of the aspects of the components of this miraculous discourse that combines the rigor of rational reasoning manifested in the proof of the possibility of resurrection and reckoning, and between the depth of protest against absolute universal values and the attractiveness of the emotional statement manifested in encouragement and intimidation, revealing its impactful argumentative dimensions, showing some aspects of the miraculous eloquence of the Qur’an The family takes into account the status of each recipient with his different mental, psychological and emotional preparations.